The effects of whey and pumpkin seed oil on blood biochemical parameters of liver function and lipid profile in rats chronically drinking low concentrations of ethanol - Radić, Ivan; Nestorović, Vojkan; Mijović, Milica; Tatalović, Nikola; Joksimović, Bojan; Lukić, Vera; Mitić, Miloš; Adžić, Miroslav; Blagojević, Duško; Veličković, Stefan; Bulajić, Sonja; Đerković, Branislav; et al. (Archives of Biological Sciences, 2018)
Paper description: Ethanol in alcoholic drinks causes liver injury. Cow whey and pumpkin seed oil have shown hepatoprotective effects in many studies. The effects of whey and pumpkin oil supplementation on the blood biochemical parameters of liver function in male Wistar rats subjected to chronic daily intake of 12% ethanol ad libitum were examined. Ethanol consummation in small doses for 6 weeks changed lipid metabolism, but did not induce extensive liver damage. Both whey and pumpkin seed oil showed some protective potential, but pumpkin seed oil and whey together with ethanol elevated lactate dehydrogenase. Abstract: We studied the effects of whey and pumpkin seed oil supplementation on the biochemical parameters in blood serum of male rats after chronic ad libitum alcohol consumption. The levels of AST, ALT, total bilirubin, ALP, LDH, triglycerides, total cholesterol, HDL, LDL, VLDL, triglyceride/HDL ratio, total cholesterol/HDL ratio (cholesterol ratio) and LDL/HDL ratio (index of atherosclerosis) were determined in rats after six weeks of treatment with: (i) ethanol (12% ethanol, ad libitum), (ii) whey (2 g/kg per day), (iii) pumpkin seed oil (2 mL/kg per day), (iv) both ethanol and whey, and (v) both ethanol and pumpkin seed oil. The results showed no changes in the levels of AST, ALT, total bilirubin, ALP, total cholesterol, HDL and VLDL in alcoholic rats when compared to the controls (fed with a standard laboratory diet ad libitum) and rats supplemented with whey and pumpkin seed oil. Our results suggest that alcohol consumption in small doses for 6 weeks changes lipid metabolism and significantly elevates the LDL/HDL ratio (index of atherosclerosis) but does not induce extensive liver damage. Ethanol consumption in our experimental conditions lowered the triglyceride level as well as the triglyceride/HDL ratio, suggesting lipid redistribution and the induction of some cardio-protective effect. However, ethanol induced a higher index of atherosclerosis. Pumpkin seed oil showed some protective potential in alcoholic rats by lowering the total cholesterol/HDL ratio, but it elevated the LDH. Whey consumption prevented elevation of the atherosclerosis index, pointing to its protective role, probably through the redistribution of lipids. However, whey in combination with ethanol elevated LDH. https://doi.org/10.2298/ABS180320014R Received: March 20, 2018; Revised: March 30, 2018; Accepted: March 30, 2018; Published online: April 17, 2018 How to cite this article: Radić I, Nestorović V, Mijović M, Tatalović N, Joksimović B, Lukić V, Mitić M, Adžić M, Blagojević D, Veličković S, Bulajić S, Đerković B, Mirić M, Janićijević-Hudomal S. The effects of whey and pumpkin seed oil on blood biochemical parameters of liver function and lipid profile in rats chronically drinking low concentrations of ethanol. Arch Biol Sci. 2017;70(3):…